Looking through: the use of the free indirect subjetive camera in contemporary cinema - Fabiana Maceno Domingos Pedrolo (Travessias, 2021)
This research proposes to explore the cinematographic universe from the perspective of director and therefore it uses the free indirect subjective camera (a term from Italian filmaker Pier Paolo Pasolini) in contemporary cinema to illustrate the influence of Poetry Cinema today. The hybridity presente in current Productions allows this resource to help in the production of the meanings of diegesis in a peculiar way. Thus, in this article, its is intended to point out some examples of free indirect subjective found in current movie in order to presente its relevance for the construction of the work, the viewer’s perception and, mainly, its collaboration with regard to the gaze the director about the movie and its implications for the whole. Based in Pasolini theory, the focus of this article is to analyze the elements of poetry inserted in cinema having as its main tool the use of the camera. Furthermore, we will approach the theory of Tofalini (2013) on the lyrical novel, Ferreira (2004) on the poetics of cinema and Pier Paolo Pasolini on the Poetry Cinema and we wil seek to point out the brushstrokes of poetry presente in contemporary cinema by analyzing movie Mother! (2017), directed by Darren Aronofsky. Is it possible in current Productions to identity the cinema of poetry? If postmodernity is hybrid, Where can we highlight this specif aspect as a constitutive element in cinematographic narrative?